Manajemen Supervisi Akademik Kepala Sekolah Terhadap Guru Untuk Meningkatkan Mutu Pembelajaran - Lisnawati Lisnawati (THE JOER: Journal Of Education Research, 2022)
This research was conducted on the basis of the phenomenon of the problems that occur in the field related to non-optimal school principal academic supervision to carry out the management has been unable to create a good teacher performance to improve the quality of learning.The purpose of this study was to gain an overview of the principal academic supervision teacher to improve the quality of learning ranging from planning, implementation, evaluation and follow-up. The main theory is used as a tool of analysis in this study is education management theory, management theory and theory sepervisi academic quality of learning. The object of research is the headmaster, teachers, students, and supervisors within the Ministry of Religious Bandung District. The research was conducted using a qualitative approach with descriptive analytic method. The author go into the field and communicating with data sources through interviews, observation, and documentation within the Ministry of Religious Bandung District.The results of the data described in accordance with the formulation of the problem and research objectives. Based on the findings of this study concluded that the headmaster implement academic supervision through stages: planning activity by means of systematic planning and preparation, for example: set a schedule, goals, objectives academic supervision, prepare assessment instruments ability of teachers in planning teaching and learning activities, implementing the learning process and assessing teaching and learning;Implementation activities with individual and group techniques; Learning assessment using an assessment tool in the teacher's ability to teach, and write notes for follow-up evaluation results; Follow-up activities by providing reinforcement, support and professional development. All the activities of academic supervision headmaster is good enough. But there are things that need to be improved by the headmaster and the teachers. The headmasters had to increase the range of knowledge and skills, so that academic supervision program could be implemented more effectively.As for the teachers need to improve their performance, either through coordination with the headmaster or superintendent, or through working groups of teachers (KKG) on the cluster schools / madrasah and conduct professional development on an ongoing basis. Based on the conclusions of this study are expected in order to pay more attention to the staffs of each stage in the academic supervision in educational units into auxiliaries.